Dihydropyrimidine dehydrogenase activity correlates with fluorouracil sensitivity in breast cancer - Yu, Z.; Yang, Q.; Sun, J.; Zhen, J. (Experimental Oncology, 2007)
The fluoropyrimidine drug fluorouracil (FU) is one of the most frequently prescribed chemotherapeutic drugs for the curative and palliative treatment of various cancer patients. The identification of biological factors associated with tumors either responsiveness or resistance to FU chemotherapy, including FU, is increasingly being recognized as an important field of clinical cancer research. Aim: to analyze the relationship between intra-tumoral dihydropyrimidine dehydrogenase (DPD) level and FU chemosensitivity, as DPD is the initial and rate-limiting enzyme in the catabolism of FU. Materials and Methods: The histoculture drug response assay (HDRA) was performed for 54 patients. DPD expression was examined in 81 tumor samples from breast cancer patients received two cycles of FU-based primary chemotherapy before operation. Results: We found that intra-tumoral DPD enzyme activity was inversely correlated with FU cytotoxicity. We also revealed that low DPD expression was correlated with clinical response to FU-based primary chemotherapy. Conclusions: Our study indicated that DPD is a promising molecular maker for identifying tumor cells sensitivity in breast cancer patients receiving FU-based chemotherapy. Препарат ряда флуоропиримидина, флуороурацил (FU), является одним из наиболее часто используемых химиотерапевтических препаратов паллиативной терапии больных онкологического профиля. Определение биологических факторов, связанных с чувствительностью либо с устойчивостью опухолей к химиотерапевтическим препаратам, в том числе и к FU, является одним из наиболее важных направлений клинических исследований в онкологии. Цель: проанализировать взаимосвязь между внутриопухолевым уровнем дигидропиримидин дегидрогеназы (DPD) и чувствительностью клеток к FU, поскольку DPD является начальным и лимитирующим энзимом в катаболизме FU. Материалы и методы: определяли чувствительность к препаратам в гистокультуре (histoculture drug response assay, HDRA) у 54 пациентов. Экспрессия гена DPD изучена в 81 образце опухолевой ткани больных раком молочной железы, которым провели два цикла неоадъювантной химиотерапии с применением FU. Результаты: показано, что внутриопухолевая активность DPD обратно коррелирует с цитотоксичностью FU. Также выявлено, что сниженная экспрессия гена DPD коррелиирует с высоким клиническим ответом на первичную химиотерапию, основанную на FU. Выводы: результаты исследования дают основание считать DPD потенциальным молекулярным маркером чувствительности клеток злокачественных опухолей молочной железы к FU.